Public Health - Emerging and Re-Emerging Issues 2018
DOI: 10.5772/intechopen.78686
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Entomological Research with Focus on Emerging and Re-emerging Mosquito-Borne Infections in the Philippines

Abstract: This paper presented previous and current research efforts for medically important mosquitoes that serve as vectors of emerging and re-emerging diseases in the Philippines, in light of identifying the research gap that exists in the field of public health entomology in the country. This extensive review of the past and current research studies with regard to medical entomology and vector control also attempted to provide proper direction and insights for effective implementation of the country's vector control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The public health implication of dengue infection in the Philippines has been significant since its first recorded outbreak [1]. The high numbers of reported cases in previous years showed that it has been causing damaging effects on human lives.…”
Section: Introductionmentioning
confidence: 99%
“…The public health implication of dengue infection in the Philippines has been significant since its first recorded outbreak [1]. The high numbers of reported cases in previous years showed that it has been causing damaging effects on human lives.…”
Section: Introductionmentioning
confidence: 99%